Tacit knowledge in software testing: A systematic review - Idrus H.M.; Ali N. (IEEE Computer Society, 2023)
Information systems; Information use; Knowledge management; Influential factors; Issues and challenges; Systematic literature review (SLR); Systematic Review; Tacit knowledge; Software testing